2016
DOI: 10.1088/0741-3335/59/1/014034
|View full text |Cite
|
Sign up to set email alerts
|

Optical diagnostics of dusty plasmas during nanoparticle growth

Abstract: Carbon-based thin films deposited on surfaces exposed to a typical capacitively-coupled RF plasma are sources of molecular precursors at the origin of nanoparticle growth. This growth leads to drastic changes of the plasma characteristics. Thus, a precise understanding of the dusty plasma structure and dynamics is required to control the plasma evolution and the nanoparticle growth. Optical diagnostics can reveal some particular features occurring in these kinds of plasmas. High-speed imaging of the plasma glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…As mentioned above, a region with high emission intensity in the centre of the plasma bulk was not observed during phase II. In several other studies the emission profile typical for the γ-regime has been observed [56,116,161]. The presence of this region with high emission intensity in the plasma bulk has been linked to the formation of a void inside the plasma bulk [56,105].…”
Section: Dynamics Of the Sheathmentioning
confidence: 84%
See 4 more Smart Citations
“…As mentioned above, a region with high emission intensity in the centre of the plasma bulk was not observed during phase II. In several other studies the emission profile typical for the γ-regime has been observed [56,116,161]. The presence of this region with high emission intensity in the plasma bulk has been linked to the formation of a void inside the plasma bulk [56,105].…”
Section: Dynamics Of the Sheathmentioning
confidence: 84%
“…In several other studies the emission profile typical for the γ-regime has been observed [56,116,161]. The presence of this region with high emission intensity in the plasma bulk has been linked to the formation of a void inside the plasma bulk [56,105]. The conditions inside the void are different from the conditions in the nanoparticle loaded regions surrounding it and result in a higher emission intensity.…”
Section: Dynamics Of the Sheathmentioning
confidence: 93%
See 3 more Smart Citations